The mental image of libraries and information institutions in the Arab environment (Damascus University Journal of arts and humanities sciences, 2022)
The research aims to measure the mental image of the organization as a determinant of the beneficiary’s association with the library in the Arab environment. The researcher chose to measure the mental image of libraries and information institutions, their present and future, and their scientific and social role, where the mental image is represented in the mental connections stored in the memory of the beneficiary (who is here the beneficiary of the services The library) about the library that indicated the result of his dealings with it or the result of listening to others who have experience with it, Due to the lack of a specific and accurate framework containing data for the beneficiaries of the libraries, and in order to form the study sample, some interviews were conducted with those visiting libraries in the vicinity of the researcher's presence, and the questionnaire was published electronically on the Internet and on social media sites, to allow the views of a large group of beneficiaries from the services. Arab Libraries.The researcher used the questionnaire to collect her data, and reached conclusions indicating the existence of a direct moral correlation between the mental image of the organization and the three dimensions of correlation, and the existence of a direct relationship between the mental image of the beneficiary and the extent of his association with the library, which proves that the beneficiaries can participate in creating value and in developing the competitive strategy of the institution and contributing. In their innovation, what makes them an influential factor for the organization.
Keywords: the mental image of the organization; beneficiary engagement; Library and information center services